Collections from Colonial Australia in Berlin's Museum für Naturkunde and the Challenges of Data Accessibility - Schwarz, Anja; Möhrle, Fiona; von Mering, Sabine (Biodiversity Information Science and Standards, 2023)
German-speaking naturalists working in southeastern Australia in the mid-19th century relied heavily on the expertise of First Nations intermediaries who acted as guides, collectors, traders and translators (Clarke 2008, Olsen and Russell 2019). Many of these naturalists went to Australia because of the research opportunities offered by the British Empire at a time when the German nation states did not have colonies of their own. Others sought to escape political upheaval at home. They were welcome employees for colonial government agencies due to their training in the emerging research-oriented natural sciences that the reformed German universities offered at a time when British universities were still providing a broad general education (Home 1995, Kirchberger 2000). Wilhelm von Blandowski (1822–1878 ) and Gerard Krefft (1830–1881 ), who both worked in colonial Victoria and New South Wales, are among this group. Throughout their work, they corresponded extensively with naturalists in Berlin, exchanging specimens and ideas. But the preserved Australian animals, plants and rock samples, as well as the written and drawn records of animals and landscapes now held at the Museum für Naturkunde Berlin (MfN), are much more than objects of scientific interest. They also contain information about Australia's First Nations. The collections provide evidence of their role in collecting as well as their knowledge of the natural world, which has long been overlooked and, at least in part deliberately, made invisible by Western knowledge systems (e.g., Das and Lowe 2018, Ashby 2020). People data have been recognised as crucial for linking such collection objects with expeditions, publications, archival material and correspondence (Groom et al. 2020, Groom et al. 2022). It can thus potentially help reconstruct invisibilized Indigenous histories and knowledge. However, while the MfN keeps information about European collectors and other non-indigenous agents associated with their specimens in internal catalogues, databases and ...